2022
DOI: 10.1002/adsc.202101331
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light Induced Aerobic Coupling of Arylboronic Acids Promoted by Hydrazone

Abstract: A visible-light-induced oxidative coupling of arylboronic acids has been developed for the synthesis of biaryls. The reaction that employs polydentate hydrazones as the bifunctional catalyst works smoothly under room temperature. It is compatible with a wide range of functional group. The study of UV-Vis spectrum indicated that hydrazone and its complex with CuI show major absorptions upon visible-light, which secures the dual role of hydrazone as both ligand and photocatalyst in this reaction. Hence, the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 54 publications
0
11
0
3
Order By: Relevance
“…Transmetallation between the two aforementioned copper species would lead to a copper­(III)–acetylide complex that would undergo reductive elimination, affording the desired product 164 and restoring the catalytic copper­(I) species (Scheme ). As a note, an in situ generated photoactive copper complex resulting from the coordination of polydentate hydrazones to copper­(I) iodide has been shown to promote the visible light-induced, copper-catalyzed aerobic coupling of arylboronic acids …”
Section: Applications Of Photoactive Copper Complexesmentioning
confidence: 99%
“…Transmetallation between the two aforementioned copper species would lead to a copper­(III)–acetylide complex that would undergo reductive elimination, affording the desired product 164 and restoring the catalytic copper­(I) species (Scheme ). As a note, an in situ generated photoactive copper complex resulting from the coordination of polydentate hydrazones to copper­(I) iodide has been shown to promote the visible light-induced, copper-catalyzed aerobic coupling of arylboronic acids …”
Section: Applications Of Photoactive Copper Complexesmentioning
confidence: 99%
“…Green development has always been an eternal topic in the field of chemistry. The radical reactions, a class of new and developing reactions, have received extensive attention of chemists because of their mild conditions, rapid reactions, and diverse reaction forms. , Combining the requirements of green development and our interest in radical reactions, we develop a transition-metal-free alkylation/ipso-cyclization of activated alkynes with 4-alkyl-1,4-dihydropyridines for the preparation of 3-alkylated aza - and oxa -spiro­[4,5]-trienones, in which H 2 O provides an oxygen atom for the construction of the newly generated carbonyl group (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above experimental observations and our previous study on Cu/hydrazone catalysis, 21 a plausible reaction mechanism is proposed, as shown in Scheme 1. For the cross-coupling between anilines and arylboronic acids, complex 5 is generated by the reaction of CuCl 2 and hydrazone L 1 in the presence of a base.…”
Section: Resultsmentioning
confidence: 69%
“…As a continuation of our interest in hydrazine/hydrazone chemistry, we discovered that polydentate hydrazone together with Cu could promote visible-light-induced oxidative coupling of arylboronic acids. 21 Hydrazone/Cu complexes were proposed as active photochemical intermediates, which is supported by UV/Vis analysis. This methodology worked for a wide range of arylboronic acids, leading to the formation of various biaryl compounds (Fig.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation